Connexins and nitric oxide inside and outside mitochondria: Significance for cardiac protection and adaptation - Shvedova M. V. Maria; Anfinogenova Ya. J. Yana Jonovna; Popov S. V. Sergey Valentinovich; Atochin D. N. Dmitry Nikolaevich (2018, 2018)
Title screen